If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(2t + -3) + 8t = 7t + -5 Reorder the terms: -5(-3 + 2t) + 8t = 7t + -5 (-3 * -5 + 2t * -5) + 8t = 7t + -5 (15 + -10t) + 8t = 7t + -5 Combine like terms: -10t + 8t = -2t 15 + -2t = 7t + -5 Reorder the terms: 15 + -2t = -5 + 7t Solving 15 + -2t = -5 + 7t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-7t' to each side of the equation. 15 + -2t + -7t = -5 + 7t + -7t Combine like terms: -2t + -7t = -9t 15 + -9t = -5 + 7t + -7t Combine like terms: 7t + -7t = 0 15 + -9t = -5 + 0 15 + -9t = -5 Add '-15' to each side of the equation. 15 + -15 + -9t = -5 + -15 Combine like terms: 15 + -15 = 0 0 + -9t = -5 + -15 -9t = -5 + -15 Combine like terms: -5 + -15 = -20 -9t = -20 Divide each side by '-9'. t = 2.222222222 Simplifying t = 2.222222222
| 7x-(7x-2)= | | 80x=3000 | | 52=(2w-5)w | | m-3x=2x-p | | 180-x=112 | | 1+-18=23.9 | | 2-3x=-34 | | 102v+16v= | | 8(4)=v(10) | | -2(5t-5)+7t=4t-8 | | 8-c=-13 | | p^3-2p+2p^3= | | 2x+3y=154 | | 2(1+4n)=-10+4n | | 2ln(5-x)=7 | | 180-(6x+4)=5x | | 4y-4-3= | | 14n-17+19+9n= | | (x-5)(3x+8)=(x+10)(x-4) | | 1x+4(-1x+3)=6 | | 32+2n=8(-6+n)+4n | | 180-(6x+40)=5x | | 2n-14=18 | | 8(-5m-1)+(2+6v)2= | | -32+5x=20 | | 6-6n=-7(4n-4) | | 126=x^2-2 | | 0.2(x)(x)-1.1x+0.5=0 | | 2s-4s=36 | | 3x-31=29 | | -35+8+y=-6+14 | | 5x+45(35-4x)=45(3x-26) |